1967
DOI: 10.1002/j.1551-8833.1967.tb03502.x
|View full text |Cite
|
Sign up to set email alerts
|

Control Techniques for Coagulation‐Filtration

Abstract: When the removal of suspended solids from unsoftened surface waters is the primary objective of treatment, coagulation is all‐important. The efficiency of the plant and the quality of the treated water depend upon careful control of the process. Type and frequency of tests for controlling coagulation depend largely upon the character of the raw water and the plant design. Some parameters may be evaluated in the laboratory, while others need monitoring of the treatment equipment or the treated water at various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1968
1968
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…More recently, temperature effects on coagulation were mentioned in an article on coagulation control parameters written by Hannah et a1. 3 They conducted a limited number of coagulation studies on one water sample at various temperatures. Results indicated that under cold-temperature conditions, efficiency of turbidity removal decreased.…”
Section: Research and Technologymentioning
confidence: 99%
“…More recently, temperature effects on coagulation were mentioned in an article on coagulation control parameters written by Hannah et a1. 3 They conducted a limited number of coagulation studies on one water sample at various temperatures. Results indicated that under cold-temperature conditions, efficiency of turbidity removal decreased.…”
Section: Research and Technologymentioning
confidence: 99%
“…little quantitative data were presented. 7 With the current need to control the One major operational difficulty that water treatment plants face in attempting to meet the THM standards is related toseasonal fluctuations in water quality. For example, changes in water temperature appear to affect the kinetics and equilibrium of metal hydroxide precipitation, resulting in a potentially adverse effect on coagulation systems.…”
mentioning
confidence: 99%
“…The silting index may therefore be used to control coagulant overdosing. Shull 136 has described a procedure similar to the determination of the silting index of Hannah et al 135 He compared the time required to filter, at constant pressure, a 200-ml sample of jar test supernatant through a 0.45-fim membrane filter, to the time required to filter an equal volume of distilled water. The ratio was defined as the "filterability number", and was related to ZP measurements.…”
Section: Crc Critical Reviews In Environmental Controlmentioning
confidence: 99%
“…Hannah et al 135 evaluated the particle content of aqueous suspensions by passing the coagulated suspension through a millipore filter at constant pressure. The flow rate decreases as the test proceeds and is recorded as a function of time.…”
Section: Crc Critical Reviews In Environmental Controlmentioning
confidence: 99%